2021
DOI: 10.1063/5.0052569
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive computational and principal component analysis on various choline chloride-based deep eutectic solvents to reveal their structural and spectroscopic properties

Abstract: In this study, the quantum chemical properties, nonbonding interactions, and spectroscopic insights of a wide variety of choline chloride (ChCl)-based deep eutectic solvents were investigated employing molecular dynamics (MD), density functional theory, and spectroscopic analyses. Nine experimentally reported ChCl-based deep eutectic solvents (DESs) were selected for this study where ChCl was common in all the DESs and the hydrogen bond donors (HBDs) were varied. The most energetically favorable cluster was se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…While the wide design space offers opportunities for designing solvents for particular applications, it has also created obstacles in developing fundamental structure–property understanding. Many efforts pursuing such understanding have been carried out using a variety of techniques in recent years. ,, However, few underlying principles are available to guide the design of a DES and broad fundamental understanding of the link between composition, structure, and properties of DESs is still missing. For example, ethaline is one of the most studied DESs over the past decade, which is a 1:2 molar ratio mixture of choline chloride (ChCl) and ethylene glycol (EG).…”
Section: Introductionmentioning
confidence: 99%
“…While the wide design space offers opportunities for designing solvents for particular applications, it has also created obstacles in developing fundamental structure–property understanding. Many efforts pursuing such understanding have been carried out using a variety of techniques in recent years. ,, However, few underlying principles are available to guide the design of a DES and broad fundamental understanding of the link between composition, structure, and properties of DESs is still missing. For example, ethaline is one of the most studied DESs over the past decade, which is a 1:2 molar ratio mixture of choline chloride (ChCl) and ethylene glycol (EG).…”
Section: Introductionmentioning
confidence: 99%
“…94 They found maximum shifts for the OH functional group of Ch + after cluster formation, suggesting active participation in DES formation through hydrogen bonding with the acceptor groups of HBDs. 94 As the DES field continues to grow, the development of protic DESs may be envisioned as analogous to the protic ionic liquids (PIL) field. 95 As such, future computational studies in protic DES applications, for example, anhydrous proton-conducting electrolytes in fuel-cell technology, would require a method that could reproduce both hydrogen bonding and proton diffusion.…”
Section: Hydrogen Bondingmentioning
confidence: 97%
“… 93 Interestingly, Araujo et al also found urea's geometry to be more pyramidal (sp 3 ) in CCU compared to sp 2 planar in the crystal, which allows for a more flexible hydrogen bond network that encourages eutectic behavior 93 . Finally, Rain et al computed the IR spectra of nine different ChCl‐based DESs using ωB97XD and analyzed the results with principal component analysis (PCA) 94 . They found maximum shifts for the OH functional group of Ch + after cluster formation, suggesting active participation in DES formation through hydrogen bonding with the acceptor groups of HBDs 94 …”
Section: Quantum Mechanicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction properties of 1:1 ChCl/MA and other ChCl-based deep eutectic solvents are similar to the 1:1 ChCl/CA eutectic system that we studied in our previous study. 33 Experimental ATR-FTIR and Raman. The study employed ATR-FTIR to examine the intermolecular interactions among the constituents of eutectic solvent systems (all five ratios) and their corresponding structural characteristics (Figure S4).…”
Section: ■ Experimental Detailsmentioning
confidence: 99%